(untitled) (Indian Journal of Public Health Research & Development, 2023)
Background: Facial nerve palsy is uncommon mainly lower motor Neuron palsy but had significant involvement of Oto-laryngeal and Opthalmic complications too. Surgical innervations are the most viable way to overcome complications of Facial Nerve palsy. Method: 30 adults patients (17 left side, 13 right side) had facial palsy associated with ORL disorders were studied with CT scan, routine blood examination, to know any other pathogenesis. Examination was done to rule out tympanic membrane perforation, Herpes Zoster. Results: 13 (43.3%) Otalgia, 6 (20%) impaired hearing, 5 (16.6%) Ear discharge, 3 (10%) Dysphagia, 1 (3.33%) Jaw pain, 1 (3.33%) Nasal bleeding, 1 (3.33%) throat pain. The diagnosis involved 9 (30%) CSOM, 8 (26.6%) otitis media, 4 (13.3%) AOM, 4 (13.3%) otitis exterma, 1 (3.33%) Ramsay Hunt syndrome, 1 (3.33%) Herpes Zoster, 1 (3.33%) chronic Rhino- sinusitis uveitis / anterior, 1 (3.33%) acute tonsillitis, 1 (3.33%) sensorineural hearing loss. Conclusion: These associated complications need surgical corrections and onset of proper antibiotic treatment to have better prognosis because, it is LMN (lower Motor Neuron) palsy.